Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Berbasis Multimedia Interaktif di SMK - Imansyah, M Nur; Yusnarti, Mulya; Nurjannah, Nurjannah; Ramadhan, Ramadhan; Fitriatun, Fitriatun (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The training program at SMK Negeri 2 Dompu aims to improve teachers' abilities in developing interactive multimedia-based learning media. This training was held to overcome the challenges of using conventional learning media which is less attractive to students, as well as teachers' lack of understanding regarding educational technology which affects learning effectiveness. This program is designed so that teachers can utilize digital technology to support the implementation of the Independent Curriculum and create interactive learning that is relevant to the digital era. Program implementation includes three stages: preparation, implementation, and monitoring. In the preparation stage, a teacher needs survey was carried out and training materials were prepared which included the creation of multimedia learning media and the use of the Learning Management System (LMS) application. The implementation phase includes training in creating interactive multimedia learning media, developing materials in line with the Independent Curriculum, training in using the LMS, as well as assistance in creating interactive media using the Canva and LMS applications. Monitoring is carried out after training to evaluate the success of the program through assessing participant performance and measuring results through questionnaires and analysis. Program results showed a significant increase in teachers' understanding regarding the use of multimedia in learning, with 90% of participants reporting increased understanding and 80% successfully developing multimedia-based modules. In terms of LMS usage, 70% of participants successfully created an account and started using the platform. Increasing teachers' understanding and skills in interactive multimedia and LMS technology is very positive, helping teachers utilize technology to create more interesting and effective learning, as well as monitor student progress digitally, showing great potential in developing teacher competence to face educational challenges in the technological era.